“Análisis del Sistema Penitenciario Ecuatoriano en el Centro de Rehabilitación Social de Loja desde una Perspectiva Constitucional, Legal y Social - Abad Peña, Alonso Antonio (2016)
The Constitution of the Republic of Ecuador recognizes and guarantees for prisoners their rights and the interests of the same. In this sense, the Ecuadorian State, ensures that the defendant is developed in a supportive and appropriate environment that allows you to achieve full rehabilitation center that is located either to re-insert into society. In our country indices sentenced to imprisonment exceeds its amount on social rehabilitation centers are entitled to receive these people. Even knowing that the structure is not adequate and there is a large prison population that prevents proper rehabilitation of persons deprived of their liberty by lack of structure either this space for activities that should give as it is sports culture and education, precarious condition which prevents comply with the provisions of the law and even more so this harms those who are serving a sentence whose chances of reintegration into society is too bad because in his detention did not receive the treatment that protects and protects law. This research project aims to see how, treatment and application of the provisions of Regulation Applied to Centers for Social Rehabilitation of Ecuador in order to sersorar treatment to prisoners guaranteeing their rights and not infringing the provisions of the Constitution of our state constitution that sends prohibits and allows whose consequences will be punished administratively.